Policy Intervention Effect Research on Pesticide Packaging Waste Recycling: Evidence From Jiangsu, China - Hu, Naijuan; Zhang, Qian; Li, Chenglong; Sun, Hongwu (Frontiers in Environmental Science, 2022)
Large quantities of pesticide packaging wastes have been thrown and abandoned in farmlands and surroundings environment, which is not only difficult to degrade but also posing a potential pollution threat to agricultural produce and the ecological environment due to the high concentrations residues of pesticide. Chinese government has formulated a series of policies and measures and established some recycling pilots provinces. However, the intervention effects of different kinds of policies on pesticide packaging waste recycling by farmers’ and its mechanism were still unknown. This study took the pilot province Jiangsu Province as the example, by using Game Theory and Propensity Score Matching (PSM) model to analyze and compare the intervention effects of three kinds of pesticide packaging waste recycling policies, that is, punish, subsidy and reward, and mortgage return. The results showed that the three kinds of policies all positively affect farmers’ recycling behaviors in the pilot area. The incentive effect of the punishment policy was the weakest, and mortgage return policy was prominent with the recycling probability increasing 44.8% under a single policy. Based on these results, some policies suggestions were put forward as follows: improving farmers' cognition of environmental pollution caused by pesticide packaging waste and their awareness of environmental protection, establishing the necessary administrative punishment policy, increasing financial support and improving the standard of recycling subsidies, and vigorously promoting the mortgage return recovery policy in areas where conditions permit. So as to stimulate the willingness of pesticide users to recover independently, reduce the cost of administrative law enforcement and contribute to the construction of rural ecological civilization.